A Juridical Study on The Role of Waste Bank in Domestic Waste Management in Banyumas Regency - Kadar Pamuji; Abdul Aziz Nasihuddin; Sukirman Sukirman; Krisnhoe Kartika Wahyoeningsih; Siti Muflichah; Noor Asyik; Aditya Riza Darmawan (Faculty of Law, Universitas Jenderal Soedirman, 2021)
Community based waste management (PSBM) is a waste management approach based on community’s needs and demand and is planned, carried out (if possible), controlled and evaluated jointly by the community. An increase in population is always followed with increasing volume of waste, which requires change in the waste management especially from the old paradigm (collect – transport – dispose of) to the new paradigm of 3R concept (reduce, reuse, recycle). The 3R waste management pattern is implemented through waste bank empowerment by involving all elements of the community. Law Number 18 Year 2008 on Waste Management and Regulation of the Minister of Environment Number 13 Year 2021 on the Guidelines on Reduce, Reuse and Recycle Implementation through Waste Bank has opened the opportunity for public participation in waste management. All this times the Government of Banyumas Regency has applied waste management technical policies several times, but there is no express legal policy about the existence of Waste Bank. The Government of Banyumas Regency currently still prioritizes big scale waste management through a hangar system. The potential of Waste Bank as one waste conscious group and as an alternative whose role can be optimized especially in community-based waste reduction management has not got attention.Keywords: Role, Waste Bank, Domestic Waste.